The Influence of Competence and Motivation on the Performance of Military Personnel at Bengpuspal Puspalad - Ahmad Rasli; Rini Mulyani Sarah (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Achmad Yani, 2025)
There are still many obstacles in carrying out the main tasks of the Bengpuspal Puspalad. The Aims of this research are determined how much the avarege degree of the competency and the motivation well as the performance of the army in Bengpuspal Puspalad whether determined the influence of the competency to the performance of the army, determined the influences of the motivation to the performance of the army, and also determined the influences of both the competency and the motivation to the performance of the army in the Bengpuspal Puspalad. The research is conducted by using descriptive research with quantitative approach with disstratified random sample. The data collection techniques used were questionnaires, interviews, and documentation with 67 of sample if the army in Bengpuspal Puspalad. The results indicated that the competency, the motivation and the performance of the army in Bengpuspal Puspalad included in good categories. The statistical test showed that the competency and the motivation of the army partially and simultaneously have an influenced to the performance of the army in Bengpuspal Puspalad.